Trust But Verify: Examining the Association Between Students' Sourcing Behaviors and Ratings of Text Trustworthiness. Issue 2 (17th February 2017) - List, Alexandra; Alexander, Patricia A.; Stephens, Lori A.
Abstract : Three indicators of undergraduate students' ( n = 197) source evaluation were investigated as students completed an academic task requiring the use of multiple texts. The source evaluation metrics examined were students' (1) accessing of document information, (2) trustworthiness ratings, and (3) citation in written responses. All three indicators of source evaluation were found to differ across source type. Based on a significant interaction between source type and accessing of document information in predicting trustworthiness ratings, an additive model of trustworthiness evaluation is proposed. Specifically, we suggest that students access document information to confirm a priori, heuristic judgments of trustworthiness. A model using all three source evaluation metrics was found to be significant in predicting response quality, with the number of citations included in students' responses serving as the strongest predictor in the model.